Analysis the effect of plant growth regulator (Gibgro-20T) on seaweed Eucheuma cottonii by in vitro - Muhammad Kasnir; Khairun Nisaa; Harlina; Masyita (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
This study aims to determine the effect of the dose of plant growth regulator (PGR) Gibgro-20T on the growth of Eucheuma cottonii in-vitro. The experimental method used was a Completely Randomized Design (CRD) treatment with a Gibgro-20T dose of 0 ppm (control), 5 ppm, 10 ppm, and 15 ppm. The results showed that the highest weight growth rate (RGRW) obtained at 10 ppm PGR dose, which is 1.27% per day. Meanwhile, the highest length growth rate (RGRL) obtained at a dose of 10 ppm, which was 1.72% per day, and the highest RGRL was significantly different from the control (0 ppm) and 5 ppm but was not different real (P<0.05) with 15 ppm treatment. Using Gibgro-20T at doses of 5, 10, and 15 ppm, however, doses of 10 and 15 ppm show higher length growth.